Advertisements
Advertisements
Question
Find A if tan 2A = cot (A-24°).
Solution
Given :
tan 2A = cot (A-24°)
implies that tan 2A = tan [90° - (A -24°)]
implies that tan 2A = tan [90° - A + 24°]
implies that tan 2A = tan [114° - A ]
implies that 2A = 114° - A
implies that 3A = 114°
implies that A = `(114°)/3`
implies that A = 38°
RELATED QUESTIONS
Prove the following trigonometric identity.
`(sin theta - cos theta + 1)/(sin theta + cos theta - 1) = 1/(sec theta - tan theta)`
Prove the following trigonometric identities.
sin2 A cos2 B − cos2 A sin2 B = sin2 A − sin2 B
if `a cos^3 theta + 3a cos theta sin^2 theta = m, a sin^3 theta + 3 a cos^2 theta sin theta = n`Prove that `(m + n)^(2/3) + (m - n)^(2/3)`
`1+((tan^2 theta) cot theta)/(cosec^2 theta) = tan theta`
Write the value of `(1 + cot^2 theta ) sin^2 theta`.
If `sin theta = x , " write the value of cot "theta .`
What is the value of \[\frac{\tan^2 \theta - \sec^2 \theta}{\cot^2 \theta - {cosec}^2 \theta}\]
If x = a cos θ and y = b sin θ, then b2x2 + a2y2 =
Prove the following identity :
`(cosecA)/(cosecA - 1) + (cosecA)/(cosecA + 1) = 2sec^2A`
If x = acosθ , y = bcotθ , prove that `a^2/x^2 - b^2/y^2 = 1.`
prove that `1/(1 + cos(90^circ - A)) + 1/(1 - cos(90^circ - A)) = 2cosec^2(90^circ - A)`
If sec θ = `25/7`, then find the value of tan θ.
Prove that:
`sqrt((sectheta - 1)/(sec theta + 1)) + sqrt((sectheta + 1)/(sectheta - 1)) = 2cosectheta`
Prove that:
`(cos^3 θ + sin^3 θ)/(cos θ + sin θ) + (cos^3 θ - sin^3 θ)/(cos θ - sin θ) = 2`
If 1 – cos2θ = `1/4`, then θ = ?
Prove that `(sin^2theta)/(cos theta) + cos theta` = sec θ
The value of 2sinθ can be `a + 1/a`, where a is a positive number, and a ≠ 1.
Let x1, x2, x3 be the solutions of `tan^-1((2x + 1)/(x + 1)) + tan^-1((2x - 1)/(x - 1))` = 2tan–1(x + 1) where x1 < x2 < x3 then 2x1 + x2 + x32 is equal to ______.